2019
DOI: 10.3389/fphar.2019.01124
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of Abnormal Cannabidiol and Its Analog O-1602 in Taxol-Resistant Preclinical Models of Breast Cancer

Abstract: Cannabinoids exhibit anti-inflammatory and antitumorigenic properties. Contrary to most cannabinoids present in the Cannabis plant, some, such as O-1602 and abnormal cannabidiol, have no or only little affinity to the CB1 or CB2 cannabinoid receptors and instead exert their effects through other receptors. Here, we investigated whether the synthetic regioisomers of cannabidiol, abnormal cannabidiol, and a closely related compound, O-1602, display antitumorigenic effects in cellular models of breast cancer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 61 publications
(61 reference statements)
5
25
0
Order By: Relevance
“…In all cell lines, except MCF-10A and U-87MG, DHA-DA cytotoxicity was at least partially blocked by both of the two GPR55 antagonists used, indicating that GPR55 is a cell line independent target for cell death induction by this compound ( Figure 5 ). These data agree with the literature data on the GPR55 receptor expression in these cell lines [ 4 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…In all cell lines, except MCF-10A and U-87MG, DHA-DA cytotoxicity was at least partially blocked by both of the two GPR55 antagonists used, indicating that GPR55 is a cell line independent target for cell death induction by this compound ( Figure 5 ). These data agree with the literature data on the GPR55 receptor expression in these cell lines [ 4 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…This agrees with Abn-CBD preserving hepatocytes proliferation without inducing tumorogenesis. Interestingly, Abn-CBD has been reported to have anti-tumoral activity rather than promoting uncontrolled proliferation (47,48). Given that Abn-CBD also decreased IL-6 levels in our mice, the beneficial effects of Abn-CBD on preserving hepatocytes proliferation might be mediated through reductions in IL-6 levels.…”
Section: Discussionmentioning
confidence: 99%
“…There are also other studies where cancer cells were cultured with 10% FCS and treated with CBD or other synthetic CBD-like molecules. The results of these studies showed that CBD (5–20 μg/mL) reduced the viability of cancer cells and also had effects on other survival variables [ 6 8 , 16 ]. The cell lines used in these studies being different to the ones used in our study, could account for the different results observed.…”
Section: Limitationsmentioning
confidence: 99%